Front-Matter - Windia, Wayan P (Udayana Journal of Law and Culture; Vol 2 No 2 (2018): Encouraging Cultural Approach to Law, 2018)
We are so grateful to publish Udayana Journal of Law and Culture (UJLC) Volume 2 Number 2-July 2018. This edition chose “Encouraging Cultural Approach to Law” as the thematic issue. We have observed that law has been seen merely from a ‘pure’ legal perspective. As an example, culture is given less attention by scholars, legal practitioners, and policy-makers. Therefore, we endorse a cultural approach to be widely disseminated and to be used in addressing legal issues. First and second articles reveal the existence of a customary law that practised by traditional communities in Indonesia. The First article shows how customary law in Bali, that for decades dealing with traditional life of the customary community, has to adapt to Indonesian national law as well as modern principles of banking system, when it regulates the activity of its customary-based economic institution: the Village Credit Institution (Lembaga Perkreditan Desa/LPD). The Second article highlights the fundamental issue of how adat (customary) law is positioned in Indonesia’s Legal System. This article is very much coloured by academic and political debates on the existence of adat law before and after Indonesian independence. A concern on how to strengthen local communities, with regards to the implementation of Corporate Social Responsibility (CSR) in the field of tourism can be seen in the third article. This article presents a framework of CSR as it is regulated under Indonesian and Australian laws in a comparative way. The fourth article considers the needs to utilize a preventive cultural approach, on one hand, and a crime-based enforcement, on the other hand, to overcome the case of online sexual abuse of children in Indonesia. It argues that cultural approach will change gradually the behaviour of society, especially families, to take a proper means of supervision and control over their children when they are involved in activities in the online world. The fifth article tries to make a genuine causality link between the natural and environmental impacts of climate change which leads to the interstate migration of peoples. It explores how climate-induced migrants could be classified as refugees under international human rights law regime. I have to express my appreciation to I Ketut Tika who continuously provided a generous language assistance to UJLC. Also, we would like to thank all authors, submissioners, editors and reviewers who are scholars and professionals from Indonesia and some other countries for their generous contribution in this edition. We do expect that this edition would encourage potential audiences to submit their papers to the UJLC for the upcoming editions.